2015
DOI: 10.1242/jeb.118604
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing within antenna enables rapid implementation of feedback control for high-speed running maneuvers

Abstract: Animals are remarkably stable during high-speed maneuvers. As the speed of locomotion increases, neural bandwidth and processing delays can limit the ability to achieve and maintain stable control. Processing the information of sensory stimuli into a control signal within the sensor itself could enable rapid implementation of whole-body feedback control during high-speed locomotion. Here, we show that processing in antennal afferents is sufficient to act as the control signal for a fast sensorimotor loop. Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 64 publications
(76 reference statements)
0
13
0
Order By: Relevance
“…Running cockroaches of the species Periplaneta americana can infer the spatial distance to a wall from a strongly bent antenna that slides along the wall [41]. Antennal nerve recordings in this species suggest that afferent units of unknown origin can signal the change of tactile contact location of a bent antenna [42]. Recently, a modelling study that considered an array of strain-encoding campaniform sensilla along the flagellum showed that the 3D contact location can be decoded by a feed-forward artificial neural network trained to map the unique curvature of the stick insect flagellum to a 3D contact location [43].…”
Section: Shape Of the Flagellum As A Possible Coding Option For Contamentioning
confidence: 99%
“…Running cockroaches of the species Periplaneta americana can infer the spatial distance to a wall from a strongly bent antenna that slides along the wall [41]. Antennal nerve recordings in this species suggest that afferent units of unknown origin can signal the change of tactile contact location of a bent antenna [42]. Recently, a modelling study that considered an array of strain-encoding campaniform sensilla along the flagellum showed that the 3D contact location can be decoded by a feed-forward artificial neural network trained to map the unique curvature of the stick insect flagellum to a 3D contact location [43].…”
Section: Shape Of the Flagellum As A Possible Coding Option For Contamentioning
confidence: 99%
“…Since neural processing of antennal afferents in Periplaneta is known and takes up to 100 ms (Mongeau et al, 2015 ), we assume that the hot air stroke is also transduced in the antennae and processed in the brain roughly within analogical T US = 0.1 s. Besides, we have found MIF at ISI = 1 s and longer (ISI = 3, 5, 8 s) and no conditioned reaction at simultaneous ISI = 0 s and negative ISI = −2 s. Hence, ISI SF must fall into the interval 0–1 s. Our conclusion concerning the arrival of CS and US information into the brain is: the delay caused by magnetic transduction in the receptor cell and transmission to the respective neural center takes place at a maximum of 1.1 s, likely much shorter.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with the assumption of fast sensory transduction in magnetoreception typical for exteroreceptors in general. During high-speed locomotion, rapid transduction and processing of the information from sensory apparatus is a prerequisite for effective movement control feedback and takes from units to hundreds of milliseconds (Szyszka et al, 2014 ; Mongeau et al, 2015 ; Bhavsar et al, 2017 ). Cry’s recently reported role in arousal responses and Drosophila phototaxis (Baik et al, 2017 ) may point to a common Cry-mediated swift signaling mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The role of neural feedback in enabling escape behaviour has been studied extensively. In particular, cockroaches have been examined for their ability to follow walls using mechanosensory cues from their long antennae [20,42], avoid collisions during running by combining visual and antennal mechanosensory inputs [10], and even begin to escape from approaching predators using wind-receptive cerci in 60 ms [15,16]. These behaviours have been adopted as models for engineering control systems and sensors [43][44][45], and even inspired the development of crash avoidance systems for road vehicles [46].…”
Section: Selecting a Mechanically Mediated Strategy For A Maximal Speed Escape Transitionmentioning
confidence: 99%